2017
DOI: 10.1038/ncomms14728
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage during S-phase mediates the proliferation-quiescence decision in the subsequent G1 via p21 expression

Abstract: Following DNA damage caused by exogenous sources, such as ionizing radiation, the tumour suppressor p53 mediates cell cycle arrest via expression of the CDK inhibitor, p21. However, the role of p21 in maintaining genomic stability in the absence of exogenous DNA-damaging agents is unclear. Here, using live single-cell measurements of p21 protein in proliferating cultures, we show that naturally occurring DNA damage incurred over S-phase causes p53-dependent accumulation of p21 during mother G2- and daughter G1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
343
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 336 publications
(387 citation statements)
references
References 71 publications
28
343
0
3
Order By: Relevance
“…Finally, our work is consistent with the observation that the memory of cell cycle duration is lost when a cell divides, as evidenced by the lack of correlation between mother and daughter phase durations (Froese, ; Absher & Cristofalo, ; Sandler et al , ; Barr et al , ). Work by Sandler et al suggests that this apparent stochasticity is driven by underlying deterministic factors that operate on a different timescale than the cell cycle.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Finally, our work is consistent with the observation that the memory of cell cycle duration is lost when a cell divides, as evidenced by the lack of correlation between mother and daughter phase durations (Froese, ; Absher & Cristofalo, ; Sandler et al , ; Barr et al , ). Work by Sandler et al suggests that this apparent stochasticity is driven by underlying deterministic factors that operate on a different timescale than the cell cycle.…”
Section: Discussionsupporting
confidence: 91%
“…We next introduced the DNA damaging agent neocarzinostatin (NCS) to mother cells and measured the phase durations for daughter cells (Fig J, Appendix Fig S9A). Recent work in human cells has shown that DNA damage signaling in the mother cell's G2 can persist through mitosis to lengthen the duration of G1, suggesting that coupling of maternal G2 and daughter G1 could potentially arise under genotoxic stress (Arora et al , ; Barr et al , ; Yang et al , ). As expected, at the highest NCS dosages that permitted cells to finish a cell cycle without permanent arrest, we confirmed that DNA damage significantly lengthened G1 in daughter cells (Fig K, Appendix Fig S8P).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, while the proximal cause of entry into the quiescent CDK2 low state has a deterministic component, a key upstream trigger for entry into the CDK2 low state arises at least in part from stochastic errors during DNA replication. A similar conclusion was also reached by (Barr et al, 2017). …”
Section: Discussionsupporting
confidence: 87%
“…Live-cell imaging measures DNA damage checkpoint dynamics under unperturbed conditions without artificial manipulations such as cell synchronization, which can introduce unwanted DNA damage. Furthermore, the PCNA-based approach also provides an accurate methodology crucial for locating cell cycle transitions and commitment points (Barr et al , 2016, 2017; Wilson et al , 2016). This method provides an advantage over the widely-used fluorescence ubiquitin cell cycle indicator (FUCCI) system (Dowling et al , 2014; Sandler et al , 2015; Wilson et al , 2016) and its newer version (FUCCI4) (Bajar et al , 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Recent live-imaging studies in single cells have shed light on some of the underlying parameters that confer differential sensitivity to endogenous DNA damage. For example, cell-to-cell variation in p21 levels leads to differences in checkpoint stringency (i.e., the robustness of cell cycle arrest in response to DNA damage) (Arora et al , 2017; Barr et al , 2017). However, the underlying parameters that result in differential responses within a cell cycle phase and in response to exogenous DNA damage are generally unknown.…”
Section: Introductionmentioning
confidence: 99%